RANCANG BANGUN ALAT TERAPI REMATIK BERBASIS ARDUINO UNO DILENGKAPI DENGAN HEATER PAD - Dimas Riski Saputra; Wahyudi, Bayu; Rofi'i, Mohamad (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2025)
Rheumatism, or rheumatoid arthritis, is an autoimmune condition that causes chronic inflammation of the joints, especially in the hands, feet, or other frequently used parts. This inflammation usually causes pain, swelling, and limited movement, which reduces the quality of life of sufferers. One of the therapy methods that is widely used to reduce the symptoms of rheumatism is heat therapy, because heat can improve blood flow, relax muscles, and reduce joint stiffness. This Rheumatism Therapy Tool has 2 features, namely warming the waist with a DC Heater and providing an electrostimulator to the back with a pulse issued by the L298 N module. The temperature inputted into the Arduino IDE program, namely 50o Celsius, is expected to be able to provide warmth and comfort to Rheumatism therapy patients. The 3 modes that are run, namely LOW Mode, Medium Mode and High Mode, provide different pulse delays issued by the L298N driver so that patients can adjust their comfort level. The results of data analysis from measuring the power supply output are 4.51 V, 9% error percentage. Microcontroller input measurement 4.98V, 0.4% error message. The measurement of the L298N driver output is 23.9V, within the specification data range. The measurement of the DC Heater input is 4.98V, the error message is 0.4%. So from the results of the analysis, the tool is suitable for use because it is still within the safe tolerance limit. Based on data collection with an operating time of 15 minutes, the temperature shown on the Tool compared to the thermocouple has a small difference, it can be said that during operation for 15 minutes with a temperature setting of 50 Celsius it operates well and stably. Based on data collection with an operating time of 25 minutes, the temperature shown on the Tool compared to the thermocouple has a small difference, it can be said that during operation for 25 minutes with a temperature setting of 50 Celsius it operates well and stably.